Anti-inflammatory and antioxidant activity of Syzygium polyanthum (Wight) walp - Sabandar, Carla Wulandari; Juriyati Jalil,; Norizan Ahmat,; Nor-Ashila Aladdin,; Nik Khairunissa Nik Abdullah Zawawi,; Sahidin, Idin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Syzygium polyanthum has been used as folk medicine to treat ailments related to oxidative stress and inflammation. In this study, the anti-inflammatory and antioxidant activity of stem bark and root bark of the plant were investigated. The experiments that have been carried out were estimation of total phenolic and total flavonoid in the methanol extracts and fractions of both parts, isolation and structure elucidation of chemical compounds, anti-inflammatory activity evaluation based on inhibition of prostaglandin E2 production in the LPS-induced human whole blood using radioimmunoassay technique as well as antioxidant activity based on assays by using free radical scavenging DPPH and FRAP. Results showed high amounts of phenolics and flavonoids in both parts of S. polyanthum. Seven compounds were succesfully isolated from the stem bark and identified as stigmasterol (1), 8-hydroxy-6-methoxy-3-pentylisocoumarin (2), 3,3’-di-O-methylellagic acid (3), methylgallate (4), asiatic acid (5), arjunolic acid (6), and daucosterol (7). The ethyl acetate fraction of the root bark showed potent inhibitory activity on the production of PGE2 (IC50 3.03 ± 0.83 μg/mL). The methanol extract of the stem bark displaying promising DPPH scavenging activity (SC50 = 2.82 ± 0.1 μg/mL) and FRAP activity (7.02 ± 0.1 μg/μg of equivalent trolox amount). Compounds 1, 5, 6 and 7 showed pronounced inhibitory activity on the PGE2 production with IC50 ranging from 0.052 to 1.25 μM. Meanwhile, compound 4 exhibited antioxidant activity toward DPPH (SC50 10.60 μM) and FRAP (20.5 ± 1.0 μg/μg). The study concluded that S. polyanthum as a potential source for therapeutic agents with anti-inflammatory and antioxidant activities.